Structure-Function Implications in Alzheimer's Disease: Effect of Aβ Oligomers at Central Synapses - Cerpa, Waldo; Dinamarca, Margarita C.; Inestrosa, Nibaldo C. (Current Alzheimer Research, 2008)
Alzheimer's disease (AD) is the most prevalent neurodegenerative disease in the growing population of elderly people. A characteristic of AD is the accumulation of plaques in the brain of AD patients, and theses plaques mainly consist of aggregates of amyloid β-peptide (Aβ). All converging lines of evidence suggest that progressive accumulation of the Aβ plays a central role in the genesis of Alzheimer's disease and it was long understood that Aβ had to be assembled into extracellular amyloid fibrils to exert its cytotoxic effects. This process could be modulated by molecular chaperones which inhibit or accelerate the amyloid formation. The enzyme Acetylcholinesterase (AChE) induces Aβ fibrils formation, forming a stable complex highly neurotoxic. On the other hand, laminin inhibit the Aβ fibrils formation and depolymerizate Aβ fibrils also. Over the past decade, data have emerged from the use of several sources of Aβ (synthetic, cell culture, transgenic mice and human brain) to suggest that intermediate species called Aβ oligomers are also injurious. Accumulating evidence suggests that soluble forms of Aβ are indeed the proximate effectors of synapse loss and neuronal injury. On the other hand, the member of the Wnt signaling pathway, β-catenin was markedly reduced in AD patients carrying autosomal dominant PS-1. Also, neurons incubated with Aβ revealed a significant dose-dependent decrease in the levels of cytosolic β-catenin an effect which was reversed in cells co-incubated with increasing concentrations of lithium, an activator of Wnt signaling pathway. Wnt signaling blocks the behavioural impairments induced by hippocampal injection of Aβ, therefore the activation of Wnt signaling protects agains the Aβ neurotoxicity. Here we review recent progress about Aβ structure and function, from the formation of amyloid fibrils and some molecular chaperones which modulate the amyloidogenesic process to synaptic damage induce by Aβ oligomers.
Keywords: Alzheimer' s disease